Thermal analysis on the pyrolysis of tetrabromobisphenol A (TBBPA) and Electric Arc Furnace Dust mixtures - Al-Harahsheh, Mohammad; Al-Otoom, Awni; Al-Jarrah, Muhannad; Altarawneh, Mohammednoor; Kingman, Sam (Springer, 2017)
The pyrolysis of Tetrabromobisphenol A (TBBPA) mixed with Electric Arc Furnace Dust (EAFD) was studied using thermogravimetric analysis (TGA) and theoretically analysed using thermodynamic equilibrium calculations. Mixtures of both materials with varying TBBPA loads (1:1, and 1:3) were prepared and pyrolyzed in a nitrogen atmosphere under dynamic heating conditions at heating rates of 5 and 10 ⁰C/min. The mixtures degraded through several steps including decomposition of TBBPA yielding mainly HBr, bromination of metal oxides, followed by their evaporation in the sequence of CuBr3, ZnBr2, PbBr2, FeBr2, MnBr2, KBr, NaBr, CaBr2 and MgBr2, and finally reduction of the remaining metal oxides by the char formed from decomposition of TBBPA. Thermodynamic calculations suggest the possibility of selective bromination of zinc and lead followed by their evaporation leaving iron in its oxide form, while the char formed may serve as a reduction agent for iron oxides into metallic iron. However, at higher TBBPA volumes, iron bromide forms, which can be also evaporated at a temperature higher than those of ZnBr2 and PbBr2. Results from this work provide practical insight into selective recovery of valuable metals from EAFD while at the same time recycling the hazardous bromine content in TBBPA.